2013
DOI: 10.4103/0019-5413.108928
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplastic fibroma of ulna: Excision and reconstruction of olecranon with a fibular graft

Abstract: Desmoplastic fibroma is a rare, well differentiated, locally aggressive fibrous tumor usually arising from soft tissues, and rarely from bones. Involvement of forearm bones is extremely unusual. We present a large desmoplastic fibroma of right ulna in a 15-year-old male. The tumor was excised with a wide margin, and the bony defect was reconstructed with nonvascular autologous fibular graft. Reconstruction of the olecranon process was attempted using the fibular head and the remaining olecranon. At 2-years fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Both the patients from the above-mentioned studies are now free of pain. Goyal et al [ 12 ] reported a large DF in the right ulna of a 15-year-old male. The tumor was excised with a wide margin, and the bony defect was reconstructed with nonvascular autologous fibular graft.…”
Section: Discussionmentioning
confidence: 99%
“…Both the patients from the above-mentioned studies are now free of pain. Goyal et al [ 12 ] reported a large DF in the right ulna of a 15-year-old male. The tumor was excised with a wide margin, and the bony defect was reconstructed with nonvascular autologous fibular graft.…”
Section: Discussionmentioning
confidence: 99%
“…Although there have been reports of osteochondroma primary giant cell tumors and Ewing's sarcoma of the ulna. Salvaging the limb following an ulnar tumor resection poses a complex reconstructive challenge [8][9][10][11] options include resection arthroplasty, arthrodesis, resection-replantation [12], autografts [13,14], allografts [15], endoprostheses and radius neck-to-humerus trochlea transposition. Windrager and et al Recommend resection-replantation, in wich the tumor-bearing area is resected as a cylindrical segment and the distal arm is replanted with shortening [12].…”
Section: Discussionmentioning
confidence: 99%
“…Malignant and aggressive tumors located within the ulna are relatively rare, although there have been reports of osteosarcoma, primary giant cell tumors and Ewing's sarcoma of the ulna. Salvaging the limb following an ulnar tumor resection poses a complex, reconstructive challenge ( 6 , 7 , 9 11 ). Various options have been reported for the reconstruction of the elbow joint following ulnar tumor resections, such as radius neck-to-humerus trochlea transposition, endoprosthetic reconstruction, allografts, vascularized fibular grafts and extracorporeal irradiation ( 6 , 7 , 9 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Preservation of the proximal half of the olecranon during excision has been performed for the treatment of proximal ulna tumors. Goyal et al ( 11 ) reported a case of a desmoplastic fibroma of the proximal ulna that was treated with excision and reconstruction of the olecranon with a fibular graft. Bone-to-bone repair is often successful when a small region of the proximal olecranon may be preserved in continuity with the tendon insertion.…”
Section: Discussionmentioning
confidence: 99%